ASSESSING THE EFFICACY OF LABORATORY IN ENHANCING STUDENT COMPETENCY: A COMPREHENSIVE EVALUATION - Erma Kusumawardani; Akhmad Rofiq; Sujarwo Sujarwo (Program Studi PGSD Universitas Flores, 2025)
Laboratories in higher education not only function as practice spaces, but also as experiential learning platforms that play a crucial role in enhancing student competency. This study employed a descriptive approach with a CIPP (Context, Input, Process, Product) evaluative design in nine laboratories at the Faculty of Education and Psychology, Yogyakarta State University, through focus group discussions (FGDs), observations, and interviews. The results indicate that laboratories contribute positively to students' skills, creativity, and self-development, but still face limitations in terms of human resources, infrastructure, and the absence of national competency standards governing learning outcomes. The implications of this study emphasize the urgency of developing competency-based education (CBE) laboratories through improved facilities, managerial capacity, and nationally recognized competency certification, so that laboratories can function optimally as centers for competency development that are competitive both nationally and internationally.